Sources of free radicals and oxidative stress in the oral cavity - Żukowski, Piotr; Maciejczyk, Mateusz; Waszkiel, Danuta (Archives of oral biology, 2018)
•The oral cavity is subjected to various environmental factors.•The oral cavity is a place especially susceptible to oxidative damage.•One of the major ROS sources is periodontal inflammation.•Oxidant sources in the oral cavity include also: food, dental treatments and materials. An oral cavity is a place especially susceptible to oxidative damage. It is subjected to many environmental pro-oxidative factors or factors that have the ability to generate reactive oxygen species (ROS). The aim of this article is to present the main sources of ROS and oxidative stress in the oral environment. A literature search was performed using the PubMed and Google Scholar databases. One of the most important ROS sources in the oral cavity is periodontal inflammation. Other sources of ROS include: xenobiotics (ethanol, cigarette smoke, drugs), food (high-fat diet, high-protein diet, acrolein), dental treatment (ozone, ultrasound, non-thermal plasma, laser light, ultraviolet light), and dental materials (fluorides, dental composites, fixed orthodontic appliances, and titanium fixations). It has been shown that excessive production of ROS in the oral cavity may cause oxidative stress and oxidative damage to cellular DNA, lipids, and proteins, thus predisposing to many oral and systemic diseases. Recognition of the exogenous sources of ROS and limitation of exposure to the ROS generating factors can be one of the prophylactic measures preventing oral and systemic diseases. It is suggested that antioxidant supplementation may be helpful in people exposed to excessive production of ROS in the oral cavity system.